Association of depression and anxiety with health-related quality of life in beginning Medical Sciences Student - Nilufar Marufi; Roghayeh Malekzadeh; Fatemeh Naderi; Maryam Garmabi; Ahmad Sharifnezhad; Fatemeh Darrudi; Zahra Andishmand; Ali Gholami (Scientific Reports)
Abstract The present study sought to examine the association between depression and anxiety with health-related quality of life (HRQoL) among clinical and non-clinical medical students. This study was conducted on newly entrance students (2019 and 2020) in Neyshabur University of Medical Science (NUMS). 471 students participated in this cross-sectional study. The Beck Depression (BDI-II), Anxiety Inventory (BAI), and SF-12 questionnaires were used. To assess the correlation between depression, anxiety, and HRQoL, the Pearson correlation was used. The independent t-test was performed to evaluate the association among different variables with HRQoL. Further, a multiple linear regression model was used to control the confounding effects of the covariates. The mean age of the study population was 21.9 (SD = 6.1), majority of them were female (62.4%). More than 21% and about 32% of students had mild to severe levels of depression and anxiety, respectively. According to correlation analysis (Pearson’s r), the correlations between depression, anxiety, and total HRQoL were relatively strong and negative. The multiple linear regression model revealed a statistically significant association between depression and anxiety with different subscales, components, and total HRQoL (p < 0.05). It has been confirmed that the different levels of depression and anxiety in medical students are negatively associated with HRQoL.